Improving Patient Safety in General Hospitals Using Structured Handoffs: Outcomes From a National Project - Toren, Orly; Lipschuetz, Michal; Lehmann, Arielle; Regev, Gil; Arad, Dana (Frontiers in Public Health, 2022)
Background: Promoting quality and patient safety is one of the health policy pillars of Israel’s Ministry of Health. Communication among healthcare professionals is of utmost importance and can be improved using a standardized, well-known handoff tool such as the Introduction, Situation, Background, Assessment, Recommendations (ISBAR) framework. The purpose of this article is to present the implementation process and results of a national project that used a standardized tool for team communication. Methods: This national interventional project included process-implementation teams from 17 general hospitals in Israel. Interventions focused on communication between nursing and medical staff members using the ISBAR instrument when transferring patients from intensive care units to medical or surgical wards. The project evaluation was based on the participants’ assessment of and satisfaction with the handoff process. Results: A positive response to the use of the ISBAR instrument during handoffs was found in all aspects of the instrument that were examined. At the conclusion of the project, fewer team members reported experiencing a lack of significant information, and more team members reported better data flow and fewer communication errors. A greater number of team members also reported using a uniform form. Nurses expressed more satisfaction than did physicians at the conclusion of the project. No changes in satisfaction were found among physicians. Conclusions: Implementation of a safety project at a national level requires careful planning and the close involvement of the participating teams. A standardized instrument, a well-defined process, and external controls to monitor and manage the project are essential for success. Disparities found in the responses of nurses versus physicians suggest the need for a different approach for each profession in planning and executing a similar project in the future.